Social factors enhancing students’ positive attitudes toward entrepreneurial intention: an exploratory study - Azman Ismail,; Hidayati Ernida Hassan Azahari,; Saida Farhanah Sarkam, (Pusat Pengurusan & Pembangunan Mahasiswa, Universiti Kebangsaan Malaysia, 2018)
Entrepreneurship intention amongst students had become a major debate since the 2000s when university students were encouraged to create their own employment instead of being employed. Students’ attitude toward entrepreneurship intention is influenced by social factors, namely subjective norm and role model. Although this relationship has been extensively studied, the role of social factors as an important determinant is less discussed in the entrepreneurship education research literature. Thus, this study was undertaken to evaluate the relationship between social factors and students’ positive attitudes toward entrepreneurial intention. A survey method was employed to collect data from economic and business students at a Malaysian public research university. The outcomes of the analysis revealed that social factors act as an important determinant of students’ positive attitudes toward entrepreneurial intention in an organization.